Pack-Boriding of Monel 400: Microstructural Characterization and Boriding Kinetics - Gunen, Ali; Keddam, Mourad; Erdogan, Azmi; Karakas, Mustafa Serdar; Erdoğan, Azmi (Korean Inst Metals Materials, 2022)
Monel 400 was pack-borided in the temperature range of 1173-1273 K for exposure times of 2-6 h. The boride layers produced on the surface of the alloy were examined by scanning electron microscopy and phase identification was carried out by X-ray diffraction. The topmost layer on the borided Monel 400 was compact and contained the Ni2B phase while the diffusion zone contained grain boundary precipitates of borides. Boride layers of 35-290 mu m thickness and 1002-1476 HV0.025 hardness were obtained. SEM observations revealed a smooth interface between the boride layer and the diffusion zone. A kinetic model based on the integral method was applied to investigate the kinetics of Ni2B layer. The boron activation energy in the Ni2B layer was estimated as equal to 300.7 kJ mol(-1). An experimental validation of the model was made by comparing the experimental layer thicknesses obtained, after boriding at 1198 K for 1 and 3 h, with predicted values. [GRAPHICS] .
Keywords: Superalloy; Monel 400; Boriding; Integral Diffusion Model